AB1156-HPR Do Rheumatic Patients under Biological Therapy Receive More Attention from Their Doctors Compared with Those Who do not Receive Such Therapy?. (10th June 2014) - Dobroiu, M.; Vasile, D.; Ioan, C.; Moca, J.; Dragan, M.; Ciobanu, M.; Zamfira, M.; Aproianu, C.; Predeteanu, D.; Ionescu, R.; Berghea, F.
Abstract : Background: Chronic rheumatic patients come in contact with health system more often than regular people that give them the opportunity to better identify both the strengths and weakness of this system. Rheumatic patients that receive biological therapy (BIOTh) are a special group of chronic patients usually having more severe diseases and a potential for additional complications throughout their disease. Independent of these, rheumatic patients receiving biologics are frequent subjects of observational studies including various types of medical registers. Sometime they are compared with rheumatic patients that do not receive biological treatment (nBIOTh) but do these two different kind of patients receive same attention from the medical system? If the answer is different from yes then we might experience a bias in these studies. Objectives: To evaluate a possible difference between BIOTh and nBIOTh in terms of medical attention these groups receive. Methods: We used a standardized patient satisfaction survey to perform an indirect measurement of the medical attention received by every patient. The surveys covers eight distinct areas split in 23 items: patient's needs, existence of coordinated medical help, easiness of access to medical care, support for information, physical comfort, emotional support, support for proper family relationship, global perception. The survey was conducted in three academic hospitals. Data analysis was done by using SPSS 19 software. Results: A number of 84 patients have been included in BIOTh group and 44 in nBIOTh group. No significant difference in terms of underling disease, education, sex and access to medical services was found between groups. Mean age was a little bit higher in nBIOTh than in BIOTh: 52, 2 (13, 5) vs 50, 2 (13, 2) years but we considered this difference not significant for the purpose of this study. We found a systematic difference between groups that favor BIOTh as following: in 7 of the 23 items evaluated, the patient satisfaction was significant higher in case of subjects under biological therapy, in the remaining 18 items no statistical difference occurred; no item favored patients without biological therapy. The difference was even higher when BIOTh group was restricted to those subjects with more than two years of biological therapy. Conclusions: Our results suggest that chronic rheumatic patients on biological therapy seems to receive more attention than rheumatic patients that do not receive such therapy. This conclusion is particularly important for those observational studies that compare data from patients exposed and not exposed to biological therapy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2282